Influence of cheese making process on STEC bacteriophage release - Mangieri, Nicola; Vieira, Rui P.; Picozzi, Claudia (Frontiers in Microbiology, 2023)
Shiga toxin-producing Escherichia coli (STEC) are foodborne pathogens implicated in diseases including hemolytic uremic syndrome (HUS) and hemorrhagic colitis (HC). The main virulence factor are Shiga toxins; their production and secretion are by-products of the expression of late genes of prophages upon sub-lethal environmental stimuli exposure. Hence, the lysogenic prophage after a stress switch to lytic cycle spreading the Stx phages. In the present study, 35 STEC were screened for the presence and the ability to release Shiga toxin-encoding bacteriophages. Three bacterial strains showed signals of prophage presence both in plate and in PCR. Subsequently, these bacterial strains were subjected to stressors that simulate cheese manufacturing conditions: NaCl (1, 1.5 and 2% w/v), lactic acid (0.5, 1.5 and 3% v/v), anaerobic growth, pasteurization (72°C for 15 s), UV irradiation. The ability to release prophage was evaluated by Real Time qPCR. Induction of the prophages showed that the addition of NaCl at 1.5 and 2% significantly increased viral release compared to control. Conversely, the addition of lactic acid had a significant repressive effect. The other applied stressors had no significant effect in phage release according to the experimental conditions adopted.